Monitoring health related quality of life in adolescents with diabetes: a review of measures. Issue 5 (20th April 2007) - de Wit, M; Delemarre-van de Waal, H A; Pouwer, F; Gemke, R J B J; Snoek, F J
Abstract : Particularly in chronic conditions, monitoring health related quality of life (HRQoL) of adolescents in clinical practice is increasingly advocated. We set out to identify and review the clinical utility of available generic and diabetes specific HRQoL questionnaires suitable for use in adolescents with type 1 diabetes. Four generic and five diabetes specific questionnaires were identified and evaluated. The responsiveness of most instruments warrants further research and standardisation of HRQoL measurement should be sought to facilitate comparisons across centres and countries. The PedsQL and the KINDL-R appear, at this time, to be the most suitable instruments.